Not Telling the Truth in the Patient–Physician Relationship - Silva, Carlos Henrique Martins Da (Bioethics, 2003)
The presence of truth and honesty is a permanent demand, and becomes vital the more committed and intimate a relationship is. Medical practice is relevant to this discussion when one questions whether or not a physician should always tell their patient the truth in the face of a progressive or potentially fatal disease, regarding the diagnosis, outcome, therapy and evolution of the specific disease. From this discussion we aim, with the present report, to look at the truth applicable to the patient-physician relationship, and its ethical and moral implications; and also to look at where the Brazilian Code of Medical Ethics (BCME) and the medical literature stand regarding this issue. One concludes that there are only two moments not to tell a patient the truth: when the patient does not want to be informed, and when the truth could be iatrogenic. The question now is, when would the truth be iatrogenic? Physicians, in our opinion, would not be able to judge solitarily when the truth might be deleterious to their patient. Alternatively, we propose the appointment of a multidisciplinary commission to help the doctor with such a decision.